Black Strings and String Clouds Embedded in Anisotropic Quintessence: Solutions for Scalar Particles and Implication - Deglmann, Maria de Lourdes (Cadernos de Astronomia, 2026)
In this work, we show that the radial solutions of the Klein-Gordon equation in an AdS spacetime composed of a black string, surrounded by both a matter distribution analogous to a string cloud and an anisotropic quintessence fluid, exhibit the occurrence of so-called dark phases, which are induced by the presence of the quintessential fluid. These dark phases are possible quantum observables for spin−0 particles located near theblack string’s event horizon.
Keywords: Dark Energy; Quintessence; Scalar Particle; Heun Equations